TEACHING READING COMPREHENSION BY USING RECIPROCAL TEACHING APPROACH - Juliana Juliana (Universitas Syiah Kuala, 2016)
The objective of this study was to investigate the effect of using the reciprocal teaching approach in teaching reading comprehension to the second grade (year 11) students of SMA Negeri 2 Lhoksukon. This study employed a true experimental design in which there were two classes as the sample, one as the experimental and the other as the control class. The experimental group was taught by using the reciprocal teaching approach, while the control group was taught by using the teacher centered approach. In collecting the data, a test and a questionnaire were used, and then the collected data were analyzed by using Statistical Product and Service Solution (SPSS) Version 22. Before the data were processed into further inferential statistics, the normality and the homogeneity of the data were examined. The results of the normality and homogeneity tests showed that the data were normal (sig. 0.20 and 0.12) and homogeneous (sig. 0.63). Based on the t-index from the analysis, it was found there was a significant difference between both groups as 0.17 is higher than α=0.05. The findings indicate that the students taught by using the reciprocal teaching approach achieved significantly better scores in reading comprehension than those taught by using the teacher centered approach. Hence, the alternative hypothesis was accepted and the null hypothesis was rejected. Moreover, the result of the data analysis from the questionnaire indicated that almost all the students responded positively towards the use of the reciprocal teaching approach since it effectively improved their reading comprehension skills.